Digital literation to increase health awareness: a case of mediteranian diet - Tulloh, Munaja (Institute for Advanced Science, Social, and Sustainable Future, 2023)
The heart disease is usually caused by various bad habits such as smoking, rarely exercising, having an unhealthy diet, as well as the habit of consuming alcohol. Coronary heart disease is ranked as a deadly disease with the additional data that some people aged over 15 years have cholesterol, triglyceride and LDL levels that are above normal. Students who study at tertiary institutions and become students who migrate and live in dormitories or boarding houses, the majority have unhealthy eating patterns, either due to lack of attention from parents, freedom to choose food, lazy to cook, or limited funds. For this reason, it is necessary to have a strategy that can be implemented by students as an effort to maintain heart health. One way to do this is by modifying your diet. Diet modification is an activity to reduce or replace unhealthy food intake with healthier food. In college students, awareness of maintaining a healthy diet must be instilled so that in the future, especially in old age, they do not have unwanted diseases due to wrong lifestyles in their youth. For this reason, as a student, you must be very aware of the importance of maintaining health, especially heart health by changing patterns eat to be healthier by consuming lots of fiber intake. This food modification can be realized through the implementation of a diet in the form of a Mediterranean diet.